1993
DOI: 10.1029/93gl01080
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐isotope study of ozone: Implications for the heavy ozone anomaly

Abstract: Laboratory experiments have been performed with O and O2 in their ground electronic states to study the distribution of all possible ozone isotopes formed. Results show that with respect to 48O3 the two symmetric molecules 17O17O17O and 18O18O18O are depleted, in good agreement with standard recombination theory. A large enrichment of about 18% is found in the asymmetric molecule 16O17O18O, while all others carry about 2/3 of that. A comparison with past laboratory and stratospheric ozone isotope measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 25 publications
(16 reference statements)
8
86
0
Order By: Relevance
“…The other is an effect arising from the difference of zeropoint energies of the two exit channels of a dissociating ABB* formed from A + BB, where A and B are different isotopes of O. In this second isotope effect (24,25) the low-pressure recombination rate constants for the formation of ozone isotopologues ABB* from A + BB are studied under "isotopically unscrambled conditions" (8), namely, where an effort is made to avoid complications from follow-up reactions of the products of the dissociated ABB* with other species. It was shown (8)(9)(10)(11)(12)) that this very interesting ΔZPE effect cancels under conditions ("isotopically scrambled conditions") where the MIF is studied experimentally and cancels for a physically understood reason.…”
Section: Key Experimental Results To Be Explained By An Mif Theorymentioning
confidence: 99%
“…The other is an effect arising from the difference of zeropoint energies of the two exit channels of a dissociating ABB* formed from A + BB, where A and B are different isotopes of O. In this second isotope effect (24,25) the low-pressure recombination rate constants for the formation of ozone isotopologues ABB* from A + BB are studied under "isotopically unscrambled conditions" (8), namely, where an effort is made to avoid complications from follow-up reactions of the products of the dissociated ABB* with other species. It was shown (8)(9)(10)(11)(12)) that this very interesting ΔZPE effect cancels under conditions ("isotopically scrambled conditions") where the MIF is studied experimentally and cancels for a physically understood reason.…”
Section: Key Experimental Results To Be Explained By An Mif Theorymentioning
confidence: 99%
“…It was also found that the enrichment is mainly located in the asymmetric isotopomers (Mauersberger et al, 1993). The rate coefficients of many individual isotopic combinations in reaction (R1) have been measured (Anderson et al, 1997;Janssen et al, 1999;Mauersberger et al, 1999), and it was found that there is a strong dependence of the rate coefficient of (R1) on the change in zero-point energy in the equivalent exchange reaction O+O 2 → O * 3 → O 2 +O (Janssen et al, 2001).…”
Section: Introductionmentioning
confidence: 90%
“…A chemical coupling to 03 is an attractive process from which to derive a large mass-independent fractionation because a variety of measurements have shown that stratospheric 03 is significantly enriched in •aO, typically by of the order of 100%o relative to air 02 [Goldman et al, 1989;Irion et al, 1996;Meier and Notholt, 1996], but occasionally by more than 400%o [Mauersberger, 1981]. Importantly, these enrichments are mass-independent, with the •70 enrichments typically being equal to or slightly less than the corresponding •aO enrichments [Mauersberger, 1987;Mauersberger et al, 1993;Schueler et al, 1990].…”
Section: + Hv --> O(•d) + 02 ;L < 315 Nm (1) Co2 + O(•d) --> Co3' (2)mentioning
confidence: 99%